Dampak Kompetensi dan Penempatan Jabatan terhadap Produktivitas Kerja Aparatur - Ahmad Haikal Taliwang; Mila Rosyana; Lina Marlina; Sarip Hidayat; Tajudin Tajudin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the influence of competence and job placement on employee performance within an organizational context. Competence represents the integration of knowledge, skills, abilities, and professional attitudes that enable employees to perform their duties effectively and efficiently. Job placement refers to the process of assigning employees to positions that align with their qualifications, educational background, experience, and competencies. In many organizations, employee performance is often hindered by inappropriate job placement, where individuals are assigned to positions that do not correspond to their capabilities. Such mismatches can lead to reduced productivity, lower job satisfaction, and difficulties in achieving organizational objectives. Therefo. This research employed a quantitative approach using descriptive and associative methods. Primary data were collected through structured questionnaires distributed to employees who served as respondents in the study. The collected data were analyzed using validity and reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). These statistical. The findings indicate that competence has a positive and statistically significant effect on employee performance. Likewise, job placement positively and significantly influences employee performance. Simultaneously, competence and job placement contribute significantly to enhancing employee performance. The coefficient of determination demonstrates that both variables explain a substantial proportion of the variance in employee performance. These results suggest that organizations should prioritize competency development initiatives and implement effective job placement strategies to optimize employee performance, increase productivity, strengthen organizational.